Pengaruh Akuntabilitas dan Transparansi terhadap Pengelolaan Alokasi Dana Desa pada Desa Dobo Nuapu’u Kecamatan Mego - Maria Nerviana Jawa; Konstantinus Pati Sanga; Emilianus Eo K. Goo (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
This research aims to analyze the influence of accountability and transparency on the management of village fund allocation in Gera Village, Mego District. This type of research is quantitative research with an associative approach. The sampling technique used a saturated sample where the entire population in this study was sampled and questionnaires were distributed to 32 respondents. Data analysis used multiple linear regression using the Statistical Package for the Social Sciences (SPSS) version 26. The results of this study show that partial accountability has no effect on the management of village fund allocations, while partial transparency has an effect on the management of village fund allocations, apart from simultaneous accountability. and transparency influences the management of village fund allocation.